1996
DOI: 10.1029/96jb01648
|View full text |Cite
|
Sign up to set email alerts
|

Worldwide wavelet analysis of geomagnetic jerks

Abstract: International audienceFollowing an earlier study which gives the principles of the method and an example of application to the eastern component of the magnetic field in the European region [Alexandrescu et al., 1995], detection and characterization of geomagnetic jerks using wavelet analysis is generalized to any horizontal component of the field and to a worldwide distribution (involving 97 locations) of observations. This allows for a systematic and global search for such events within the twentieth century… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
125
1
4

Year Published

2002
2002
2015
2015

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 135 publications
(137 citation statements)
references
References 21 publications
7
125
1
4
Order By: Relevance
“…For example, the 1932 jerk is local since it was mostly observed in the southern hemisphere and not seen in any European observatory. Another local jerk was detected in 1949, observed mainly in the Pacific area and in the American region (Alexandrescu et al, 1996). A more recent and local jerk occurring at 2003 was found by Olsen & Mandea (2007) by using satellite data.…”
Section: Introductionmentioning
confidence: 69%
See 2 more Smart Citations
“…For example, the 1932 jerk is local since it was mostly observed in the southern hemisphere and not seen in any European observatory. Another local jerk was detected in 1949, observed mainly in the Pacific area and in the American region (Alexandrescu et al, 1996). A more recent and local jerk occurring at 2003 was found by Olsen & Mandea (2007) by using satellite data.…”
Section: Introductionmentioning
confidence: 69%
“…The wavelet analysis is another method that has been applied to identify jerks. Alexandrescu et al (1996) used the continuous wavelet transform and found five events characterized as worldwide jerks, occurred during the last century : 1901: , 1913: , 1925: , 1969: and 1978. Some works point to more recent global jerks at 1991 (De Michelis et al, 1998 and at 1999 (Mandea et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The geometrical sense of this equation is that the wavelet transform of a homogeneous singularity has the appearance of a cone whose apex points onto the singularity for a ↓ 0 + . Equation (6) indicates that the magnitude of the wavelet transform is ∝ a α when sampled along the cone lines also called the ridge functions (see Alexandrescu et al [1995Alexandrescu et al [ , 1996 and Le Gonidec et al…”
Section: Analyzing Method: the Wavelet Responsementioning
confidence: 99%
“…Consequently, the interesting properties of the wavelet transform concerning the characterization of abrupt changes in signals [e.g. Mallat and Hwang, 1992;Herrmann, 1994;Alexandrescu et al, 1995Alexandrescu et al, , 1996 are retrieved in the wavelet response which may be used to remotely analyse the multiscale structure of acoustical interfaces [Walden and Hosken, 1986;Herrmann, 1996;Wapenaar, 1998Wapenaar, , 1999Marsan and Bean, 1999].…”
Section: Introductionmentioning
confidence: 99%